Making Live Music Count: The UK Live Music Census. Issue 5 (19th October 2020) - Behr, Adam; Webster, Emma; Brennan, Matt; Cloonan, Martin; Ansell, Jake
ABSTRACT: In 2017 we conducted the first-ever nationwide live music census, allowing for unprecedented levels of detailed, comparable data on the live music cultures of different localities. Live music censuses have been increasingly used in recent years (e.g. Melbourne, Edinburgh, Bristol) to illustrate the value of music to policymakers. This has coincided with challenging times for urban live music venues, particularly small venues and clubs. We present key census findings here, reflecting on how local contexts both shape the census process and may be informed by it, and on the growth of the idea of "Music Cities" to inform policy.